병원이미지평가에 관한 연구 - 오태형 (연세대학교 보건대학원, 1991)
[한글] 이 연구는 병원선택에 따른 의료기관별 이미지형성요인간의 차이와 속성이 다른 3개병원의 이미지평가를 하기 위하여 1990년11월5일부터 11월13일까지 그 지역에 거주하는 일반인을 대상으로 설문조사를 실시하였다. 연구결과는 다음과 같다. 1. 의료기관별 의료이용선택동기의 우선순위는 의원과 종합병원은 편리성이었고 대학종합병원은 훌륭한 의사가 있기 때문이다. 2. 설문대상병원인 병원별 긍정적 이미지는 가병원이 제일 높았고(81.8%) 다병원이 제일 낮아(49.2%) 병원의 특성에 따라 이미지 수준이 달랐다. 3. 설문대상병원인 가병원, 나병원, 다병원의 이미지요인은 병원의 특성에 따라 달랐다. 4. 일반적 특성에 따른 병원별 총체적 이미지는 성, 연령, 학력, 수입에서는 유의한 차이가 없었으나 직업과 소속의료보험에 따라 유의한 차이가 있었다. 5. 병원의 총체적 이미지에 영향을 미치는 특성에서는 '가'병원은 시설, 명성, 병원규모, 교통편리, 친근감이 유의한 변수로 '나'병원은 친근감, 의료진이 '다'병원은 청결, 병원규모, 명성이 유의한 변수이었으며 판별력과 일치율은 가병원이 77.3%, 나병원이 77.6% 다병원이 78.9%이었다. [영문] This study was conducted to identity the differents in hospital preference according to the type of medical facilities and to evaluate the image of three hospitals ; 'A' hospital is a University general hospital, 'B' hospital is a women's hospital, and 'C' hospital is a public hospital. A questionnaire survey was conducted from November 5 to November 13, 1990 and data were collected from 171 persons who lived in the defined area. The results are as follow: 1. The main reason for clinic preference was geographical accessibility ; and preference for a university hospital was influenced by the quality of the medical staff. 2. Among the three hospitals studied, 'A' hospital obtained the highest score for positive image(81.8%), and 'C' hospital obtained the lowest score(49.2%). 3. Among the individual characteristics, occupation and the type of health insurance were statistically significant, while sex, age, education and income were not significant. 4. A discriminant analysis showed that in the 'A' hospital the degree of facilities, name value, hospital size, readiness and familiarity of hospital were statistically significant factors to discriminate the total hospital image as positive or negative. In the 'B' hospital, familiarity of the hospital and aptitude of the medical staff were named, and in the 'C' hospital, cleanliness, name value of the hospital and hospital size were named as significant variables in total image ; the percent of correct classification were 77.3% in the 'A' hospital, 77.6% in the 'B' hospitla and 78.9% in the 'C' hospital.
병원행정학과/석사